(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Self-harm is a major risk factor for suicide but remains poorly documented. No data on self-harm in French-speaking Switzerland exist. To address this deficiency, the Swiss Federal Office of Public Health commissioned a specific self-harm monitoring programme. We present and discuss its implementation and first findings. METHODS Every patient aged 18–65 years presenting for self-harm to the emergency departments of the Lausanne and Neuchâtel general hospitals were included in the monitoring programme over a 10-month period (December 2016 to September 2017). Clinicians collected anonymous sociodemographic and clinical data. RESULTS The sample included 490 patients (54.9% female and 45.1% male) for 554 episodes of self-harm, showing a higher proportion of patients aged 18–34 (49.2%) than older age groups (35–49, 33.7% and 50–65, 17.1%). Patients were mostly single (56.1%) and in problematic socioeconomic situations (65.7%). Self-poisoning was the most commonly used method (58.2%) and was preferred by women (71% of females and 42.5% of males, Fisher’s exact test, p <0.001) and the majority of patients (53.3%) had experienced at least one previous episode of self-harm. The self-harm rate was 220 per 100,000 inhabitants in Lausanne and 140 in Neuchâtel. Suicidal intent was clear for 50.6% of the overall sample, unclear for 25.1% and absent for 24.3%. It differed significantly between sites (χ2(2) = 9.068, p = 0.011) as Lausanne reported more incidents of unclear intent (27.7% versus 17.4% in Neuchâtel) and Neuchâtel more incidents with absence of intent (33.1% versus 21.3% in Lausanne). In Lausanne, patients more frequently resorted to methods such as jumping from a height (11.4%) and hanging (9%) than in Neuchâtel (1.6% and 4.9%, Fisher’s exact test, p = 0.006). CONCLUSIONS Our results are globally consistent with previous research on self-harm. We found significant inter-site differences in methods, suicidal intent and self-harm rates. Our findings highlight the importance of implementing local self-harm monitoring to identify specific at-risk groups and develop targeted preventive intervention.